Smart Security System for Housing Using Website-Based MQTT - Tobing, Nindi Karynnina Luban; Rakhmania, Amalia Eka; Rasyid, Abdul (Politeknik Negeri Malang, 2024)
The housing security system is one of the aspects of implementing a security system in several house buildings which have several functions that work to secure assets in the building. Then in residential areas it is difficult to carry out intense security. This study designed a